Intumescent, catalyzed flame retardant systems for polyamide‐based powder bed fusion - Roumeliotis, Paul; Schlicht, Samuel; Drummer, Dietmar (Journal of Vinyl & Additive Technology, 2025)
Flame-retardant properties of polymer components are essential to a broad variety of applications. However, the processing of flame-retardant thermoplastics in laser-based powder bed fusion remains challenging. To overcome prevailing limitations, a new polyphosphate-based intumescent flame-retardant system for polyamide 12 (PA12) based powder bed fusion was developed. For this purpose, PA12 was successfully manufactured in selective laser sintering (SLS) with different combinations of a multi-component flame-retardant system, consisting of ammonium polyphosphate (APP), pentaerythritol (PER) and manganese(II) oxide as a catalyst with four different energy densities in the range of 0.25–0.40 J mm−3. Relying on thermal and microscopic investigations, the process window was observed to remain unaffected by the intumescent flame-retardant system. All samples show a similar thermal degradation behavior, independent of the energy density during the manufacturing process, implying no chemical nor physical alterations of the flame-retardant additives induced by higher energy densities. The flame behavior was analyzed using limiting oxygen index (LOI), UL-94, and cone calorimeter measurements in combination with thermographic imaging. Maximum LOI values of 32.2% and a UL94 rating of V0 for specimens of 2.5 mm thickness were achieved. Cone calorimeter results show a significant reduction of 39% in peak heat release rate (pHRR) compared to a benchmark flame-retardant system, significantly enhancing flame-retardant properties over existing systems across all assessed metric